Derivation of a Multilayer Approach to Model Suspended Sediment Transport: Application to Hyperpycnal and Hypopycnal Plumes (Communications in Computational Physics, 2017)
We propose a multi-layer approach to simulate hyperpycnal and hypopycnalplumes in flows with free surface. The model allows to compute the verticalprofile of the horizontal and the vertical components of the velocity of the fluid flow.The model can describe as well the vertical profile of the sediment concentration andthe velocity components of each one of the sediment species that form the turbiditycurrent. To do so, it takes into account the settling velocity of the particles and theirinteraction with the fluid. This allows to better describe the phenomena than a singlelayer approach. It is in better agreement with the physics of the problem and givespromising results. The numerical simulation is carried out by rewriting the multilayerapproach in a compact formulation, which corresponds to a system with nonconservativeproducts, and using path-conservative numerical scheme. Numerical resultsare presented in order to show the potential of the model.